Effect of feeding turmeric and amla on dressing percentage and meat bone ratio of broilers - Chandra, Gyan; Mane, Somnath Hanumant; Dhage, Sameer Ashok; Pandey, Sachin Kumar (Indian Journal of Animal Nutrition, 2019)
An experiment was conducted to study the inclusion of turmeric and amlaand its combinations on production performance, viz., weight gain, feed intake and feed conversion ratio, dressing percentage and meat bone ratio for a period of six weeks with seventy commercial, straight run day-old Vencobb-400 broiler chicks. These chicks were randomly grouped into seven treatments with ten chicks each. The treatment groups consisted of control (T0), 0.25% turmeric (T1), 0.5%turmeric (T2), 0.25% amla (T3), 0.5% turmeric (T4), 0.25% turmeric+amla (T5) and 0.5% and turmeric+amla (T6) were included in broiler diet. The weight of heart, liver and gizzard increased slightly with supplementation of turmeric and amla which were non-significant. The higher dressing percentage (72.20 %) and meat bone ratio (14.36%) were observed in T6 on per cent live weight basis. Similarly the group was more economic.